Penggunaan Presupposisi pada Konten Friends of Merry Riana di YouTube: Penelitian - Salwa Fitri Hadju; Dakia N. Djou; Nuramila (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Presupposition is part of pragmatic studies that refers to assumptions that are considered correct by the speaker or listener before producing a speech. Presuppositions play an important role in shaping the audience's understanding of the message conveyed by the speaker. Along with the development of digital media, especially YouTube, the study of presuppositions is increasingly relevant because this platform is often used to convey ideas, opinions, and information widely. Therefore, this study aims to describe the types of presuppositions, language functions, and speech intent contained in the content of